The Measurement of Fast Transient Emissions During Real World Driving - Peckham, Mark; Parnell, Jamie; Hammond, Matthew; Mason, Byron (Frontiers in Mechanical Engineering, 2020)
Some of the most challenging aspects of preparing vehicles to comply with the new RDE (Real Driving Emissions) legislation are the calibration of engines to minimise emissions during the numerous and sometimes harsh transients inherent in such conditions. Fast response emissions analyzers are necessary to resolve rapid transient emissions and have been deployed simultaneously in the engine-out and tailpipe exhaust gas of several vehicles. Data has also been logged from the vehicles’ ECUs and combined with accurate GPS data. The results show that certain road lay-outs (e.g. congested junctions and speed bumps) can provoke significant tailpipe NOx emissions; often emitting very high levels near schools where traffic calming measures have been adopted for road safety. The lean excursions and insufficient rich purge during such transients are generally shown to be the cause of such emitting events.